The effect of whole-body vibration training on selected breast cancer risk factors in obese postmenopausal women: A randomized controlled trial - Marwa Abd El- Rahman Mohamed; Doaa Rafat Elazab; Walid Ahmed Abouelnaga; Hossam Eldein Huessin Kamel; Heba Ahmed Abdeen (Universidad de Murcia, 2023)
Article accepted. The article will be published here soon. Pending final quality checks.